Electrical characterization of ZnO/NiO p-n junction prepared by the sol-gel method - Akyuzlu, A. Merih; Dagdelen, Fethi; Gultek, Ahmet; Hendi, A. A.; Yakuphanoğlu, Fahrettin (Springer Heidelberg, 2017)
ZnO and NiO films were synthesized on fluourine-doped tin oxide (FTO) glass substrate by the sol-gel method. The surface morphology of the films was investigated by atomic force microscopy. The optical band gaps of the ZnO and NiO films were found to be 3.198 and 3.827eV, respectively. A ZnO/NiO p-n junction diode was prepared and electrical charge transport mechanism of the diode was analyzed using thermionic emission and Norde functions. The ideality factor, barrier height and series resistance of the diode were determined to be 6.46, 1.036eV and 39.1 M , respectively. The obtained results indicate that ZnO/NiO p-n junction can be used as transparent diode for optic communications.
Keywords: Thin-Films; Fabrication; Nio